Workplace bullying a risk for permanent employees - Dominic Keuskamp; Anna M. Ziersch; Fran E. Baum; Anthony D. LaMontagne (Elsevier, 2012)
Abstract Objective: We tested the hypothesis that the risk of experiencing workplace bullying was greater for those employed on casual contracts compared to permanent or ongoing employees. Methods: A cross‐sectional population‐based telephone survey was conducted in South Australia in 2009. Employment arrangements were classified by self‐report into four categories: permanent, casual, fixed‐term and self‐employed. Self‐report of workplace bullying was modelled using multiple logistic regression in relation to employment arrangement, controlling for sex, age, working hours, years in job, occupational skill level, marital status and a proxy for socioeconomic status. Results: Workplace bullying was reported by 174 respondents (15.2%). Risk of workplace bullying was higher for being in a professional occupation, having a university education and being separated, divorced or widowed, but did not vary significantly by sex, age or job tenure. In adjusted multivariate logistic regression models, casual workers were significantly less likely than workers on permanent or fixed‐term contracts to report bullying. Those separated, divorced or widowed had higher odds of reporting bullying than married, de facto or never‐married workers. Conclusions: Contrary to expectation, workplace bullying was more often reported by permanent than casual employees. It may represent an exposure pathway not previously linked with the more idealised permanent employment arrangement. Implications: A finer understanding of psycho‐social hazards across all employment arrangements is needed, with equal attention to the hazards associated with permanent as well as casual employment.